'I am not a tragedy. I am full of hope': communication impairment narratives in newspapers. Issue 2 (13th November 2013) - O Malley‐Keighran, Mary‐Pat; Coleman, Mary
Abstract Background Individual attitudes and more general attitudes in society can negatively influence the functioning of people with communication disorders according to the World Health Organisation's (WHO) International Classification of Functioning, Disability, and Health (ICF) (2002). Personal narratives have been recommended as the best means to convey and understand a person's life experience and have been investigated extensively. Investigations of personal narratives of communication impairment in mass media continue to be relatively rare in the literature. Published narratives can enrich understandings of clients' experiences by elucidating available representations of lived experiences of communication impairment. Aims To answer the following research questions: What types of personal narratives of communication impairments are currently being disseminated in Irish newspapers? How are experiences of communication impairments represented in these narratives? Methods & Procedures The study was qualitative, deploying inductive analysis and drawing on Frank's (2008) typology of illness narratives to analyse narratives that were published in two Irish national newspapers over a 12‐month period. Outcomes & Results The results illustrate the under‐representation of communication impairments in Irish newspapers as ten out of 51 narratives in the corpus pertained to conditions that may have associated communication impairments. None of the narratives related the lived experience of a person with communication impairment in depth. A combination of quest and chaos narrative types was identified in six out of the ten narratives. Three out of the ten narratives featured a combination of chaos and restitution narrative types. One narrative was identified as being entirely a quest narrative. Three narratives contained elements of restitution. Inductive analysis revealed six main themes in the data (two for each narrative type) with one sub‐theme identified for each main theme. The six main themes are: positive stances, re‐evaluation of life, despair, fear, hope and support of others. Conclusions & Implications The under‐representation of the lived experience of people with communication impairments in Irish national newspapers may be seen as contributing to a general lack of understanding and awareness of communication impairments. This under‐representation, coupled with a lack of awareness, may potentially affect the ability of people with communication impairments to re‐engage with and reintegrate into their communities.